The efficacy of bidirectional barbed sutures for incision closure in total knee replacement: A protocol of randomized controlled trial. Issue 34 (21st August 2020) - Ye, Zijian; Zhu, Wengang; Xi, Xinhua; Wu, Qiang
Abstract: Background: Barbed suture is a novel type of suture introduced in different surgical specialties. Nevertheless, its effect in total knee replacement is still unclear in terms of wound complications and cost effectiveness. The purpose of the present work is to evaluate the safety and efficacy of bidirectional barbed suture in reducing postoperative wound complications in the patients undergoing total knee replacement. Methods: This prospective, randomized, and controlled study was performed from January 2017 to December 2018. It was authorized via institutional review committee of Yuebei People's Hospital (GDYB1002189). Hundred participants were divided randomly into 2 groups, namely, control group (n = 50) and the study group (n = 50), respectively. All operations were performed using the Miller-Galante prosthesis (Zimmer; Warsaw, IN). For study groups, the joint capsule (Stratafix1-0) and subcutaneous (Stratafix2-0) and intracutaneous (Stratafix3-0) tissues were sutured by a bidirectional barbed suture. At the end, extra 4 to 5 stitches were made to avoid detachment and incision rupture. For control group: the joint capsule was sutured by a traditional absorbable suture (Ethicon VICRYL* Plus 1-0), and the subcutaneous tissue was sutured by an absorbable suture (Ethicon VICRYL* Plus 2-0). The skin was sutured by staples. Incision length, suture time, operation time, postoperative length of hospital stay, and incision complications (such as effusion, infection, hematoma, and skin necrosis) were recorded. All data analyses are implemented through utilizing SPSS for Windows Version 20.0. Results: The results will be shown in Table 1. Conclusion: This study can reach a reliable evidence for utilizing bidirectional barbed suture in wound closure in total knee replacement. Trial registration: This study protocol was registered in Research Registry (researchregistry5823).